2000
DOI: 10.1021/np000175m
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Inhibitory Prenylated Xanthones and Flavones from Maclura tinctoria

Abstract: The organic extract of the plant Maclura tinctoria exhibited moderate anti-HIV activity. Seven prenylated phenolic derivatives were isolated from the active fractions and characterized by spectroanalytical methods. New compounds macluraxanthone B (1), macluraxanthone C (2), and dihydrocudraflavone B (8) were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 19 publications
2
91
0
2
Order By: Relevance
“…Macluraxanthone B isolated from Maclura tinctoria exhibited moderate anti-HIV activity and hinokiflavone isolated from methanolic extracts of twigs and leaves of Rhus succedanea showed strong inhibition of the polymerase of HIV-1 RTase in in vitro assay [39]. Hypericin obtained from Hypericum perforatum showed activity against non-human retrovirusesas well as human retroviruses in lymphocytes.…”
Section: N-butylharminementioning
confidence: 99%
“…Macluraxanthone B isolated from Maclura tinctoria exhibited moderate anti-HIV activity and hinokiflavone isolated from methanolic extracts of twigs and leaves of Rhus succedanea showed strong inhibition of the polymerase of HIV-1 RTase in in vitro assay [39]. Hypericin obtained from Hypericum perforatum showed activity against non-human retrovirusesas well as human retroviruses in lymphocytes.…”
Section: N-butylharminementioning
confidence: 99%
“…Due to their remarkable pharmacological and biological applications, their synthesis has drawn great attention in the field of medicinal and pharmaceutical chemistry. They possess antiviral [9], anti-inflammatory [10], antibacterial [11], antimalarial [12], anti-HIV [13], antimicrobial, antioxidant, and anticarcinogenic [14,15] activities. These are also used as an antagonist for paralyzing action of zoxazolamine [16].…”
Section: Introductionmentioning
confidence: 99%
“…were found to possess antiinflammatory (Chang et al, 2008), anti-lipid peroxidative (Chang et al, 1994), antioxidative Lee et al, 2006;Jeong et al, 2009Jeong et al, : 2012, hepatoprotective , antibacterial (Fukai et al, 2004), antifungal , antitumor effects and cytotoxicity against various cancer cells (Seo, et al, 2001;Zou et al, 2004;Wang et al, 2005Wang et al, : 2010Kuang et al, 2011). More extensive phytochemical and pharmacological studies, several xanthones and flavonoids as the main active components have been identified from this genus and some of them have been reported to possess significant pharmacological properties, including anti-inflammatory (Lin et al, 2012), anti-cancer Wang et al, 2010;Kuang et al, 2011), antibacterial (Fukai, et al, 2004) and anti-HIV (Groweiss et al, 2000) activities. For instance, macluraxanthone B and C isolated from Maclura tinctoria exhibited anti-HIV activity (Groweiss et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…More extensive phytochemical and pharmacological studies, several xanthones and flavonoids as the main active components have been identified from this genus and some of them have been reported to possess significant pharmacological properties, including anti-inflammatory (Lin et al, 2012), anti-cancer Wang et al, 2010;Kuang et al, 2011), antibacterial (Fukai, et al, 2004) and anti-HIV (Groweiss et al, 2000) activities. For instance, macluraxanthone B and C isolated from Maclura tinctoria exhibited anti-HIV activity (Groweiss et al, 2000). Isoalvaxanthone, a prenylxanthone, isolated from Cudrania cochinchinensis (Lour.)…”
Section: Introductionmentioning
confidence: 99%